Assessment of agricultural information needs in African, Caribbean and Pacific (ACP) States for CTA’s Products & Services: Phase 1: Pacific: Country study: Papua New Guinea - Powaseu, Ipul (Technical Centre for Agricultural and Rural Cooperation, 2004)
This study was undertaken to assess the agricultural information needs of Papua New Guinea. After presenting a country profile, the study goes on to cover information and capacity building needs, and identifying specific areas of collaboration...